2017
DOI: 10.22495/rgcv7i2art1
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study Of Stock Price Forecasting Using Nonlinear Models

Abstract: This study compared the in-sample forecasting accuracy of three forecasting nonlinear models namely: the Smooth Transition Regression (STR) model, the Threshold Autoregressive (TAR) model and the Markov-switching Autoregressive (MS-AR) model. Nonlinearity tests were used to confirm the validity of the assumptions of the study. The study used model selection criteria, SBC to select the optimal lag order and for the selection of appropriate models. The Mean Square Error (MSE), Mean Absolute Error (MAE) and Root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This nature of studies is very scarce in literature as far as South Africa is concerned. Other researchers such as Xaba et al (2015) and Alvarez et al (2018) employ the regime switching models but the focus was not on predicting the regime shifts in the JSE-ALSI. For more reading about nonlinear and regime-shifts, see Hamilton, (2010); Chkili and Nguyen (2014); Ardia et al (2018); and Wolf et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…This nature of studies is very scarce in literature as far as South Africa is concerned. Other researchers such as Xaba et al (2015) and Alvarez et al (2018) employ the regime switching models but the focus was not on predicting the regime shifts in the JSE-ALSI. For more reading about nonlinear and regime-shifts, see Hamilton, (2010); Chkili and Nguyen (2014); Ardia et al (2018); and Wolf et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…With these results, the null hypothesis is rejected, and we conclude that the behaviour of the exchange rates in SA is better explained by a proposed supervised ML model (akin to the Markov-switching generalized autoregressive conditional heteroscedasticity model). Previous empirical studies, including Xaba et al (2017) and Chkili and Nguyen (2014), found parallel results when utilizing the likelihood ratio test. From a theoretical perspective, this behaviour is normal and can be clarified by the changing economic structure in the exchange rate of SA, attributable to structural economic reform policies (financial liberalization, tax system adjustments, competition policy), as well as to progressive economical and financial crises at both local and worldwide levels.…”
Section: Regime Shifts In the Real Exchange Ratementioning
confidence: 77%
“…According to Tsay (2014), the final optimal lag length should be selected by the SBC. Xaba et al (2017) acknowledged that with a large sample size, say ≥ 30, both the SBC and Hannan-Quinn perform much better in an optimal lag length selection. With this evidence, in this study the selected optimal lag length is 1 (Table 4).…”
Section: Markov-switching Garch Frameworkmentioning
confidence: 99%
“…According to Timmermann (2000) the probability law governing the parameters fully follows the Gaussian innovation , the coefficient of an autoregressive , the two intercepts and finally the twostate transition probabilities that follow homogenous Markov Chain (MC). For further readings on MSM, consult Yang (2000); Moolman (2005); Xaba et al (2016) and Xaba et al (2017).…”
Section: Literature Reviewmentioning
confidence: 99%